Niñez, educación y pandemia: la experiencia de las familias en Buenos Aires (Argentina) - Marina Moguillansky; Carolina Duek (Desidades, 2021)
In this work, we propose to characterize the forms that education assumed in Argentina during the pandemic in order to explore the alternatives and forms in which the teachers were linked with their students, from the perspective of the families. The hypothesis that organizes this work is that the experiences of virtual education during the pandemic reproduce and aggravate the pre-existing inequalities regarding the monitoring, care, organization and adaptation of schools to virtual education. For this research, we conducted twenty semi-structured interviews with parents of boys and girls between the ages of six and nine, whose children attend public and private schools in the Metropolitan Area of ​​Buenos Aires. We inquired about their perceptions on virtual education during the pandemic and the forms of accompaniment sustained by parents, as well as the difficulties of this process